Beyond Genres and Autorship: The Affective Archive and Migrant Writing in Dani Zelko’s Work (Comparatismi, 2025)
This article analyzes Reunión (2016-2020), a project by Argentine artist Dani Zelko, as a paradigmatic case for rethinking literary genre from a comparative, expanded, and transmedial perspective. Conceived as a poetic-political device, Reunión combines oral dictation, handwritten transcription, artisanal publishing, and collective reading, generating an affective archive between voice, body, and language. Focusing on the first two seasons of the project, the article interprets Reunión as a migrant and relational practice that subverts literary hierarchies and enacts textual hospitality. It explores the tension between lyric and testimony, the performativity of communal reading, and co-authorship as a critical gesture. In this way, genre emerges as a space of displacement, resonance, and collective invention.
Keywords: Reunión; Performative Poetry; Literary Genre; Affective Archive; Migrant Writing; Comparative Literature